2015
DOI: 10.1037/hea0000185
|View full text |Cite
|
Sign up to set email alerts
|

Do single and multiple behavior change interventions contain different behavior change techniques? A comparison of interventions targeting physical activity in obese populations.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Methods: BCTs used to increase physical activity (PA BCTs) in intervention descriptions of included studies were double coded using a standardized BCT taxonomy. Interventions were categorised as SHBC (targeting physical activity) or MHBC (targeting physical activity and diet) interventions. The mean number of PA BCTs for SHBC and MHBC interventions was compared using an independent samples t-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…This provides support for schools to encourage more positive habits across all three behaviours. There is ongoing debate about whether interventions are more effective when targeted towards a single behaviour (for example physical activity) rather than multiple behaviours (for example physical activity, sedentary behaviour and sleep) [7,45,46]. A single behaviour target may be more effective in changing a single behaviour, but a strategy targeting multiple behaviours may be more effective in enhancing an outcome that is influenced by multiple behaviours, such as obesity [46] or academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…This provides support for schools to encourage more positive habits across all three behaviours. There is ongoing debate about whether interventions are more effective when targeted towards a single behaviour (for example physical activity) rather than multiple behaviours (for example physical activity, sedentary behaviour and sleep) [7,45,46]. A single behaviour target may be more effective in changing a single behaviour, but a strategy targeting multiple behaviours may be more effective in enhancing an outcome that is influenced by multiple behaviours, such as obesity [46] or academic performance.…”
Section: Discussionmentioning
confidence: 99%
“… 29 109 Systematic reviews of the effectiveness of multiple health behaviour interventions suggested that those targeting related behaviours (eg, diet and physical activity) produced greater behaviour change than those targeting unrelated behaviours (eg, smoking and physical activity), 110 and that specific intervention techniques are necessary for each behaviour. 26 Physical activity and sleep are suggested to have a bi-directional relationship, 16 yet no previous RCTs have combined physical activity and sleep in one intervention to utilise the synergistic relationship between physical activity and sleep. The Synergy Study addresses this by targeting both physical activity and sleep, simultaneously, using specific intervention techniques to enhance participants’ self-regulatory skills in relation to the two health behaviours and thus, leverages the potential for synergistic improvements in both behaviours.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Furthermore, multiple health behaviour change interventions need to implement BCT that are specific to each behaviour to produce greater changes in targeted behaviours. 26 Interventions targeting physical activity and sleep in combination therefore need to provide behaviour-specific intervention strategies to maximise change and harness the potentially synergistic effects between physical activity and sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, self-control strength model (Baumeister et al, 2000) and ego-depletion (Baumeister et al, 1998) suggests that efforts in one domain can have implications for one's capacity to self-regulate in other domains. This could cause individuals to feel over-burdened and prematurely drop out of the intervention program (Sweet and Fortier, 2010;McSharry et al, 2015). In addition, simultaneous interventions may also fail to address any behavior in sufficient depth, reducing the potential for an intervention effect (Persky et al, 2005;Prochaska and Sallis, 2004;Taylor et al, 2004).…”
Section: Introductionmentioning
confidence: 94%